1997
DOI: 10.1096/fasebj.11.1.9034170
|View full text |Cite
|
Sign up to set email alerts
|

Cystine levels, cystine flux, and protein catabolism in cancer cachexia, HIV/SIV infection, and senescence

Abstract: Patients with skeletal muscle catabolism (cachexia) fail to conserve the skeletal muscle protein and release large amounts of nitrogen as urea. Previous studies suggest that the threshold for the conversion of amino acids into other forms of chemical energy and the concomitant production of urea are regulated by the plasma cystine level and hepatic cysteine catabolism. Studies of plasma amino acid exchange rates in the lower extremities now show that healthy young subjects regulate their plasma cystine level i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 9 publications
4
40
0
Order By: Relevance
“…To ameliorate these changes and their immunological consequences, we (Dröge, 1989;Dröge et al 1992) proposed treatment with a cysteine derivative such as N-acetyl-cysteine. Subsequently, the abnormal cysteine status of HIV-infected patients and simian immunodeficiency virus-infected macaques has been confirmed by other research groups (Eck et al 1991;Staal et al 1992;Hortin et al 1994;Akerlund et al 1996;Hack et al 1997;Walmsley et al 1997). Several groups also reported a significant decrease in the intracellular glutathione level of the peripheral-blood mononuclear cells from HIV-infected patients (Eck et al 1989; Roederer et al Herzenberg et al 1997;Jahoor et al 1999) and simian immunodeficiency virus-infected rhesus macaques (Eck et al 1991).…”
Section: Massive Loss Of Cysteine In Human Immunodeficiency Virus Infmentioning
confidence: 75%
“…To ameliorate these changes and their immunological consequences, we (Dröge, 1989;Dröge et al 1992) proposed treatment with a cysteine derivative such as N-acetyl-cysteine. Subsequently, the abnormal cysteine status of HIV-infected patients and simian immunodeficiency virus-infected macaques has been confirmed by other research groups (Eck et al 1991;Staal et al 1992;Hortin et al 1994;Akerlund et al 1996;Hack et al 1997;Walmsley et al 1997). Several groups also reported a significant decrease in the intracellular glutathione level of the peripheral-blood mononuclear cells from HIV-infected patients (Eck et al 1989; Roederer et al Herzenberg et al 1997;Jahoor et al 1999) and simian immunodeficiency virus-infected rhesus macaques (Eck et al 1991).…”
Section: Massive Loss Of Cysteine In Human Immunodeficiency Virus Infmentioning
confidence: 75%
“…Depletion of branched chain amino acids has been implicated in muscle shrinkage observed in HD (5). Similarly, a pathogenic role for cysteine deficiency in HD is supported by the beneficial effects of N-acetylcysteine (8,27) and couples with evidence for cysteine disturbances in other conditions of oxidative stress including aging, neurodegeneration, AIDS, and insulin resistance syndrome (28)(29)(30)(31)(32). Disturbances of cysteine disposition in multiple diseases may reflect a form of "cysteine stress" with widespread impact.…”
Section: Discussionmentioning
confidence: 99%
“…Franklin et al have reported that the peak GSH-induced proliferation is consistently fourfold greater in splenocytes from old rats as compared to young rats when cells are stimulated with concanavalin A. The low plasma levels of cystine, one of the precursors of GSH, in old age [15] may result in high responsiveness to exogenous cystine. Although the precise mechanisms responsible for this difference are obscure, our results suggest that the GSH peroxidase-dependent detoxification system is defective in T lymphocytes from aged animals and that exogenous GSH is more effective in augmenting proliferation of splenocytes from aged animals than of those from young animals [8].…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the plasma cystine level is disrupted in conditions with progressive skeletal muscle catabolism, including cancer, HIV infection and old age [15]. Virtually all diseases in which abnormally low Open and closed bars indicate data for the control and combined administration groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation